Optimalisasi Pemberdayaan Fasilitas Kesehatan Melalui Edukasi Pelayanan Prima dan Promosi Media Digital di Puskesmas Bayan Kabupaten Lombok Utara Nusa Tenggara Barat - Shinta Desiyana Fajarica; I Wayan Suadnya; Tenri Waru (Jurnal Gema Ngabdi, 2023)
Service excellence in healthcare is critical in order to providing quality care and maintaining doctor and patient loyalty. In an effort to provide maximum service, of course, health facilities must think of excellent service as the main option to realize a perfect service quality. The Puskesmas is one of the First Level Health Facilities which is the main reference when people need first aid for health problems. The Puskesmas in this context is the first gateway for health services aimed at providing first aid to the community. The purpose of this service is to present important issues related to achieving service excellence in healthcare and the role of customer service in Puskesmas. This community service uses a controlled and participatory descriptive observational approach as well as Focus Group Discussion (FGD). The output of this community service is increasing awareness, knowledge and skills about excellent service and maximizing existing resources to provide the best service to the community. On the other hand, this dedication is also aimed at providing further understanding about promotions using digital media to facilitate service activities at the Bayan Health Center.